Ratio of Electron Donor to Acceptor Influences Metabolic Specialization and Denitrification Dynamics in Pseudomonas aeruginosa in a Mixed Carbon Medium - Zhang, Irene H.; Mullen, Susan; Ciccarese, Davide; Dumit, Diana; Martocello, Donald E.; Toyofuku, Masanori; Nomura, Nobuhiko; Smriga, Steven; Babbin, Andrew R. (Frontiers in Microbiology, 2021)
Denitrifying microbes sequentially reduce nitrate (NO3–) to nitrite (NO2–), NO, N2O, and N2 through enzymes encoded by nar, nir, nor, and nos. Some denitrifiers maintain the whole four-gene pathway, but others possess partial pathways. Partial denitrifiers may evolve through metabolic specialization whereas complete denitrifiers may adapt towards greater metabolic flexibility in nitrogen oxide (NOx–) utilization. Both exist within natural environments, but we lack an understanding of selective pressures driving evolution towards each lifestyle. Here we investigate differences in growth rate, growth yield, denitrification dynamics, and the extent of intermediate metabolite accumulation under varying nutrient conditions between the model complete denitrifier Pseudomonas aeruginosa and a community of engineered specialists with deletions in the denitrification genes nar or nir. Our results in a mixed carbon medium indicate a growth rate vs. yield tradeoff between complete and partial denitrifiers, which varies with total nutrient availability and ratios of organic carbon to NOx–. By shifting denitrification dynamics and rates, metabolic lifestyle and nutrient conditions influence the extent of nitrite accumulation, with specialists accumulating 3-fold higher nitrite under low carbon but complete denitrifiers accumulating relatively greater nitrite under low NOx–. Our model connects nutrient conditions with the evolution of metabolic lifestyle and denitrification dynamics underlying the accumulation of chemical intermediates.